Analisis Ketahanan Energi Pembangkit Listrik Tenaga Sampah (PLTSa) Metode Landfill dan Thermal di Tempat Pembuangan Sampah Terpadu (TPST) Bantar Gebang - Benny Tuahta Bangun; Robinson Purba; Hakimul Batih; stepanus stepanus (Prodi Teknik Elektro FT UKI, 2019)
The problem facing by city of Jakarta today is the increasing volume of waste, reaching 7,000 tons per day sent to Bantar Gebang TPST which is currently not handled properly. The purpose of this research was to analyze the application of Landfill and Thermal Waste Power Plant (PLTSa) in Bantar Gebang TPST from the perspective of Energy Security by measuring Energy Supply Security Index (ESSI) using 4 dimensions and 5 approach indicators : Availability (Indicator: Working hour per year), Accessability (Indicator: Access to technology), Affordability (Indicator: Cost of generation per kWh) and Acceptability (Indicator: Avoided CO2 Emission kg per MWh and percentage reduction in waste volume per day). Energy security analysis results are obtained: aspects of availability with working hour indicators per year: PLTSa Landfill = 0.95, PLTSa Thermal = 0.98; aspects of accessibility with ease of technology access indicators: PLTSa Landfill = 0.74, PLTSa Thermal = 0.58; affordability aspects with indicators of the cost of electricity generation: PLTSa Landfill = 0.99, PLTSa Thermal = 0.983; aspects of accessability with two indicators, avoided (CO2) emission: PLTSa Landfill = 1.0, PLTSa Thermal = 0.14, and the percentage of waste reduction: PLTSa Landfill = 0.50, PLTSa Thermal = 0.85.